New anti-proliferative agent, MK615, from Japanese apricot “Prunus mume” induces striking autophagy in colon cancer cells in vitro - Mori, Shozo (World J Gastroenterol, 2007)
AIM: To investigate the anti-neoplastic effects of MK615, an extract from the Japanese apricot (Prunus mume), against colon cancer cells. METHODS: Three colon cancer cell lines, SW480, COLO, and WiDr, were cultured with MK615. Growth inhibition was evaluated by cell proliferation assay and killing activity was determined by lactate dehydrogenase assay. Induction of apoptosis was evaluated by annexin V flow cytometry. Morphological changes were studied by light and electron microscopy, and immunofluorescence staining with Atg8. RESULTS: MK615 inhibited growth and lysed SW480, COLO and WiDr cells in a dose-dependent manner. Annexin V flow cytometry showed that MK615 induced apoptosis after 6 h incubation, at which point the occurrence of apoptotic cells was 68.0%, 65.7% and 64.7% for SW480, COLO, and WiDr cells, respectively. Light and electron microscopy, and immunofluorescence staining with Atg8 revealed that MK615 induced massive cytoplasmic vacuoles (autophagosomes) in all three cell lines. CONCLUSION: MK615 has an anti-neoplastic effect against colon cancer cells. The effect may be exerted by induction of apoptosis and autophagy.